Positive Islet Cell Cytoplasmic Antibody and Long-Term Use of Lipid-Lowering Agents Are Positively Correlated With Peripheral Atherosclerosis in Patients With Autoimmune Diabetes: A Cross-Sectional Study - Xinyue Chen; Jie Yu; Yiwen Liu; Xuechen Wang; Fan Ping; Wei Li; Huabing Zhang; Lingling Xu; Yuxiu Li (Journal of Diabetes Research)
Conclusions: The correlation between positive ICA and atherosclerosis suggests inflammation at an early stage plays a role in macrovascular complications in autoimmune diabetes. The association between long-term use of lipid-lowering agents and atherosclerosis suggests the need for early screening and intervention for dyslipidemia in patients with autoimmune diabetes.